Thailand : 2013 Article IV Consultation. (IMF Staff Country Reports; Country Report ;, 2013)
This 2013 Article IV Consultation highlights that in 2012, Thailand's economy rebounded strongly from the devastating floods, with real GDP growing by 6.5 percent. Private consumption rose 6.7 percent, reflecting pent-up demand and government measures, including the rice pledging scheme, where the government was committed to buying rice from farmers at a set price above the prevailing market price, and the first-car buyer scheme. On the back of reconstruction spending, private investment grew by 14.4 percent. With growth driven by domestic demand, the current account surplus is expected to reach a small deficit of 0.2 percent of GDP in 2014.